Kedudukan Hukum Islam Dalam Sistem Hukum Civil Law Dan Common Law Di Indonesia - Nurainun; Nurul Febriyani Harahap; Nisa Andriani Regar; Dwi Agus Pranata; Nisa Nurhasanah Purba; Sri Hadiningrum (Sharia Journal and Education Center Publishing, 2024)
This research discusses the influence of Islamic law on the development of the civil law and common law systems in Indonesia, a country founded on the rule of law with diverse ethnicities, cultures, and religions. With a majority Muslim population, Islamic law plays a significant role in complementing the legal certainty of the civil law system through substantive justice values, such as in the regulation of waqf and zakat. In the common law system, Islamic law is accommodated formally or informally depending on the societal context. The research employs a normative juridical method, which refers to analyzing legal norms and concepts relevant to the issues being studied. Data sources are obtained through literature studies, including journal articles, books, and previous research. The findings indicate that Islamic law holds an essential role in both civil law and common law systems. In the civil law system, Islamic law complements legal certainty with values of substantive justice, as seen in the regulations of waqf and zakat. Meanwhile, in the common law system, Islamic law is formally or informally accommodated, depending on the majority or minority Muslim context of a given society.